Identification and Overexpression of a Knotted1-Like Transcription Factor in Switchgrass (Panicum virgatum L.) for Lignocellulosic Feedstock Improvement - Wuddineh, Wegi A.; Mazarei, Mitra; Zhang, Ji-Yi; Turner, Geoffrey B.; Sykes, Robert W.; Decker, Stephen R.; Davis, Mark F.; Udvardi, Michael K.; Stewart, C. Neal (Frontiers in Plant Science, 2016)
High biomass production and wide adaptation has made switchgrass (Panicum virgatum L.) an important candidate lignocellulosic bioenergy crop. One major limitation of this and other lignocellulosic feedstocks is the recalcitrance of complex carbohydrates to hydrolysis for conversion to biofuels. Lignin is the major contributor to recalcitrance as it limits the accessibility of cell wall carbohydrates to enzymatic breakdown into fermentable sugars. Therefore, genetic manipulation of the lignin biosynthesis pathway is one strategy to reduce recalcitrance. Here, we identified a switchgrass Knotted1 transcription factor, PvKN1, with the aim of genetically engineering switchgrass for reduced biomass recalcitrance for biofuel production. Gene expression of the endogenous PvKN1 gene was observed to be highest in young inflorescences and stems. Ectopic overexpression of PvKN1 in switchgrass altered growth, especially in early developmental stages. Transgenic lines had reduced expression of most lignin biosynthetic genes accompanied by a reduction in lignin content suggesting the involvement of PvKN1 in the broad regulation of the lignin biosynthesis pathway. Moreover, the reduced expression of the Gibberellin 20-oxidase (GA20ox) gene in tandem with the increased expression of Gibberellin 2-oxidase (GA2ox) genes in transgenic PvKN1 lines suggest that PvKN1 may exert regulatory effects via modulation of GA signaling. Furthermore, overexpression of PvKN1 altered the expression of cellulose and hemicellulose biosynthetic genes and increased sugar release efficiency in transgenic lines. Our results demonstrated that switchgrass PvKN1 is a putative ortholog of maize KN1 that is linked to plant lignification and cell wall and development traits as a major regulatory gene. Therefore, targeted overexpression of PvKN1 in bioenergy feedstocks may provide one feasible strategy for reducing biomass recalcitrance and simultaneously improving plant growth characteristics.